Introduction to thermoacoustic devices - Biwa, Tetsushi (Hackensack, NJ : World Scientific, 2021)
"Oscillations of gas and/or liquid columns in a flow channel can lead to various phenomena such as Stirling cycle heat engines, pulse tube refrigerators, as well as thermally induced gas oscillations like Sondhauss tube and Rijke tube. Although those phenomena may look different from each other, they can be universally described by the concepts of work flow and heat flow. Work flow stands for the acoustic power used in acoustics. Heat flow is the energy flow associated with the hydrodynamic transport of entropy. These energy flows help us to understand the thermoacoustic phenomena and construct acoustical heat engines. The book aims to provide a comprehensive overview of how the oscillations of gas and/or liquid columns make possible the mutual energy conversions between work flow and heat flow through thermal interactions between fluids and channel walls. The thermodynamic aspects of energy flows are highlighted by introducing Lagrangian point of view to explain the thermodynamic cycles that the fluid parcels undergo. The relevant experimental results are provided to verify the theoretical analysis based on basic equations of fluid dynamics"--
Preface -- Various thermoacoustic devices -- Wave propagation in a tube -- Quality factor of acoustic resonance tube -- From acoustics to thermoacoustics -- Basic equations of sound waves in a pipe and their solutions -- Components of energy flows and work source and their classification -- Work source -- Heat flow -- Future prospects -- Bibliography -- Index.
Includes bibliographical references and index.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: Heat exchangers; Heat -- Transmission; Acoustic emission; Electronic books